SOPs as part of the quality system - Nicholas, Steve (Henry Stewart Talks, 2013)
The need for SOPs, Requirements of SOPs, Quality related terminology, Process capability, SOP as a trainee manual, The large volume of a paper-based system, Information on demand, FDA deficiencies – A traditional vs. a process based approach, Uniformity of performance, SOP in a traditional quality system, SOP developed by function, Independent quality department, Modern, robust quality management system, DMAIC approach to continual improvement, Process mapping, Identification of gaps, Incorporation into the workflow, Mistake proofing (Poka yoke), FlyBy airlines and the online booking system example, Flow of the processes, Documentation of key processes – SOP software, SOPs and the new generation